The Use of Virtual Reality in the Assessment of Paranoid Thoughts: A Comparison with Desktop-Based Tools. Issue 4 (31st December 2019) - Şoflău, Radu; David, Daniel
Abstract: Although virtual reality systems (VR) are being increasingly used to assess paranoid thoughts, there is a scarcity of data concerning the relative usefulness of VR for investigating these symptoms. The current study aimed to compare the usefulness of VR with that of a less expensive desktop-based tool for assessing paranoia. One hundred and twenty-six participants (mean age = 21.42 years, SD = 4.38, range = 18, 47; 81.8% female) were recruited for this study. After completing measures of trait paranoia and of a number of theoretical predictors of paranoia, participants were randomly assigned to a VR or a desktop-based assessment of paranoid thoughts. An identical neutral social scenario was implemented in both conditions. Results showed that unlike desktop-based assessments (F(1, 64) = 2.01, p = .161, partial ŋ 2 = .03), VR assessments indicated higher levels of paranoid thoughts among individuals with high levels of trait paranoia than among those with low levels of trait paranoia (F(1, 64) = 5.49, p = .022, partial ŋ 2 = .08), but only for one measure of paranoid thoughts. For the other measure, results followed a similar pattern, but the interaction between trait paranoia and the type of environment was not significant (F (1, 65) = 3.57, p = .052). Moreover, both measures of paranoid thoughts used in VR were significantly related to trait paranoia and a large number of predictors (p < .05), while just one measure of paranoid thoughts used in the desktop environment was significantly associated with trait paranoia and solely one of the tested predictors (p < .05). In addition, individuals assessed in VR reported higher levels of cognitive absorption than those assigned to a desktop-based assessment. Overall, findings of the present study suggest that VR may be better suited for the investigation of paranoid thoughts than desktop-based tools.